THE INFLUENCE OF JOB STRESS TOWARDS EMPLOYEE NEGATIVE BEHAVIOR WITH SELF-ESTEEM AS THE MODERATOR AND MEDIATOR - Septian, Ecsan (Jurnal Manajemen Update, 2019)
ABSTRACTEmployee negative behavior is one of the most problems that inflict a loss which been found in an organization or firm worldwide. The cause of this global issue has been traced down by researchers for decades and it leads to the well documented direct effect of job stress on negative behavior. However, the previous theoritical explanation and empirical findings of the relationship has been inconsistent with the level of negative behavior. This inconsistency brings a question whether negative behavior is only caused by job stress, which in several research found that there is a possibility of the internal attitude of self as another trigger. This study aims to examine the relationship between job stress, employee negative behavior, and negative self esteem, also to explore the moderation effect of negative self esteem on the relationship between job stress and employee negative behavior. Using sampling method, 100 questionnaires have been collected from eligible samples in the area of Pontianak, Indonesia. SmartPLS 3.0 was used for Structural Equation Model Partial Least Square (SEMPLS) analysis to test the validity, reliability, and hypotheses in this research. The study found that there is a postitive relationship between job stress and employee negative behavior, job stress and negative self esteem, and negative self esteem and employee negative behavior. This study also found that negative self esteem has the positive impact towards the influence of job stress and employee negative behavior.  Keyword : Job stress, Employee negative behavior, Negative self esteem, Moderating effect, SEMPLS